2005
DOI: 10.1634/stemcells.2004-0047
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Cord Blood Collection Method Achieves Sufficient Cell Levels for Transplantation in Most Adult Patients

Abstract: Umbilical cord blood transplantation (UCBT) has been used increasingly in both pediatric and adult patients. The total nucleated cell (NC) dose infused is the most critical factor in determining speed of engraftment and survival. Using standard collection techniques, the mean NC content of UCB units is about 10 × 10 8, and only 25% of these units reach the target cell dose of 2 × 10 7 /kg in UCBT patients weighing 50-70 kg. We have designed a modified placental/umbilical two-step collection method in which a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
36
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 53 publications
6
36
0
Order By: Relevance
“…These results are consistent with most of the previous reports (Donaldson et al 1999;Yamada et al 2000;Li et al 2001;George et al 2006;Mancinelli et al 2006), including that meconium in the amniotic fluid correlates with better cell counts (Askari et al 2005). Therefore the total LD cells per CB unit analyzed in the present study can be assumed as a substitute variable instead of the total nucleated cells in some previous studies (Lasky et al 2002;Mohyeddin Bonab et al 2004;Solves et al 2005), and can be also confirmed by other previous studies (Pafumi et al 2001;Bornstein et al 2005). In addition, the univariate analyses also show the significantly positive correlations between neonatal birth weight, placental weight, net weight of CB, and gestational age (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with most of the previous reports (Donaldson et al 1999;Yamada et al 2000;Li et al 2001;George et al 2006;Mancinelli et al 2006), including that meconium in the amniotic fluid correlates with better cell counts (Askari et al 2005). Therefore the total LD cells per CB unit analyzed in the present study can be assumed as a substitute variable instead of the total nucleated cells in some previous studies (Lasky et al 2002;Mohyeddin Bonab et al 2004;Solves et al 2005), and can be also confirmed by other previous studies (Pafumi et al 2001;Bornstein et al 2005). In addition, the univariate analyses also show the significantly positive correlations between neonatal birth weight, placental weight, net weight of CB, and gestational age (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…The authors suggested that the multi-step RWV bioreactor could expand a single cord blood to reach 1.2 9 10 9 MNC, enough to transplant an 80 kg patient (with the minimal amount of 1.5 9 10 7 CMN/kg). However, the cell dose is below the standards defined in the current guidelines for transplantation (Bornstein et al 2005). The National Aeronautics and Space Administration (NASA) developed two RWV bioreactors for tissue mass culture (Martin and Vermette 2005).…”
Section: Rotating Wall Vesselsmentioning
confidence: 99%
“…Umbilical cord blood (UCB) is other major source of HSC, which has been successfully used for transplantation since 1989 (Gluckman et al 1989). The possibility of creating UCB banks is a reality (Bornstein et al 2005); therefore UCB is increasingly gaining attention as a reliable source of HSC for transplantation, and it is currently an accepted therapy for several diseases. Bone marrow and peripheral blood stem cells autologous transplantation reduces the risk of immunological rejection and are preferred as therapeutic approaches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Therefore, several groups are working on an optimized collection procedure in order to increase the number of transplantable progenitors. Bornstein et al 2 have demonstrated recently that a modified in utero/ex utero two-step collection procedure can lead to a significant increase in the number of harvested progenitor cells.…”
mentioning
confidence: 99%